Speech Quality Analysis For Two-Ways Radio Subjected To Wind Induced Noise - Hashim, Mohd Khairul Rabani (2015)

(untitled)
Wind induced noise generated from winds flow over two-way radio can reduce communication effectiveness. There are three objectives in this study which are effect of the radio’s angle orientation toward air flow, sound quality analysis of speech signal under different wind speed and Intelligibility of the received speech signal at different threshold hearing level. Measurement of sound quality for input signal was carried out inside an anechoic chamber by using LMS measurement system. Effect of the radio’s angle orientation toward air flow was studied by used a pair of radios where a unit was placed inside a wind tunnel and the other was placed inside the anechoic chamber in order to isolate it from external noise. Angle orientation of the transmitter radio was varying for seven positions ranges from 0° to 90° with 15° increment. Sound quality analysis of speech signal under different wind speed was carried out by located a speaker at a 30cm away from the transmitter to provide an speech signal input to the radio while the wind speed varied from 0 to 10 m/s with 2 m/s increment. Sound quality base on psychoacoustics parameters of sound pressure level, roughness, sharpness, loudness, annoyance and articulation index. Threshold controller was used to attenuate the background and winds induce noise from the received signal. It was controlled at 0 to 10% with 2& increment toward highest peak of the received signal. The results show the angle lead to worst wind noise effect was 90° toward leading edge. The results show that the loudness of the wind noise increase and the roughness decreases with the wind speed. The sharpness level is fluctuated along the measurement period. The articulation index xv also decreases with the wind speed. Combinations of psychoacoustics parameters are performing annoyance level which was increasing as the wind speed increase. The threshold controller’s performance was measured in sound pressure level and articulation index. Both of measurements show good development with the controller level. Conclusion, angle orientation of radio toward wind flow and the speed of wind are highly influent to sound quality of received signal. Threshold controller is one of the ways to reduce wind speed especially for low wind speed.